Partial agonists of dopamine receptors: receptor theory and the dopamine hypothesis of psychosis. (March 2023) - Cookson, John; Pimm, Jonathan
SUMMARY: This article discusses dopamine partial agonism, which is the main mechanism of action of the psychiatric drugs aripiprazole, brexpiprazole and cariprazine. It outlines the principles of receptor theory and the structure of dopamine receptors; characterises agonists, antagonists and partial agonists; and summarises the dopamine hypothesis of psychosis and the role of dopamine and serotonin in depression.